The value relevance of financial instruments disclosure: evidence from Jordan. Issue 4 (5th December 2016) - Tahat, Yasean; Dunne, T.; Fifield, S.; Power, D.
Abstract : Purpose: The purpose of this paper is to: examine the value relevance of financial instruments disclosure (FID) provided by Jordanian listed companies under International Financial Reporting Standard (IFRS 7) as compared to that supplied under IAS 30/32; provide evidence about the value relevance of high vs low levels of FID; and investigate which components of FI-related information are more value relevant. Design/methodology/approach: A sample of 70 Jordanian listed companies is used in this monograph. A disclosure index checklist was constructed to measure FI information provided by the sample companies. In addition, a valuation model is employed to test the association between FID and market value. Findings: Although evidence is provided that FI information was value relevant over the two periods of investigation, the information supplied after the implementation of IFRS 7 was more strongly associated with market values. An analysis of the sub-components of FID reveals that the details about balance sheet, fair value and risk information matter when valuing equity. Overall, the results indicate that investors value FI-related information when making their equity pricing decisions. The result suggests that compliance with IFRS mandatory disclosure requirements does produce relevant financial statements. Research limitations/implications: The results of the current study have a number of implications for policy makers. First, they provide a great deal of insight for the IASB about the relevance of its standards to countries outside the western context. In addition, the findings provide valuable insights for policy makers in Jordan who are concerned about the implications of mandatory disclosures. Originality/value: The analysis of FID in developing countries in general, and in Jordan in particular, has been overlooked by the extant literature and therefore this study is the first of its kind to examine this research issue for a sample of Jordanian firms.